INNOVATIVE EDUCATIONAL IDEAS AND MODERN PEDAGOGICAL TECHNOLOGIES IN JADID TEACHINGS (International journal of artificial intelligence, 2026)
This article analyzes the innovative educational views of Jadid enlighteners and their compatibility with modern STEAM pedagogy. The ideas of Jadids concerning new-method schools, practical education, independent thinking, and interdisciplinary integration are interpreted from the perspective of the methodological foundations of contemporary STEAM education. Furthermore, the article scientifically reveals the relevance of Jadid pedagogy within the modern educational system.